A novel small-molecule activator of unfolded protein response suppresses castration-resistant prostate cancer growth. (28th April 2022) - Chen, Huang; Miao, Ying; Bian, Aiwu; Ye, Jiangnan; Wang, Jing; Cong, Xiaonan; Jian, Shuyi; Yi, Zhengfang; Liang, Lin; Sun, Zhenliang; Yang, Fan; Ding, Tao
Abstract: Androgen receptor-targeted therapy improves survival in castration-resistant prostate cancer (CRPC). However, almost all patients with CRPC eventually develop secondary resistance to these drugs. Therefore, alternative therapeutic approaches for incurable metastatic CRPC are urgently needed. Unfolded protein response (UPR) is regarded as a cytoprotective mechanism that removes misfolded proteins in rapidly proliferating tumor cells. However, acute activation of the UPR directly leads to tumor cell death. This study has shown that WJ-644A, a novel small molecule activator of UPR, potently inhibited the proliferation of prostate cancer cells and caused tumor regression with a good safety profile in multiple animal models. Mechanistically, we have identified that WJ-644A induced cell methuosis and autophagy upon UPR activation. Our study not only identifies the UPR as an actionable target for CRPC treatment, but also establishes WJ-644A as a novel UPR activator that has potential therapeutic value for CRPC. Highlights: WJ-644A exhibits potent efficacy against CRPC in vitro and in vivo . Our study identifies the UPR as an actionable target for CRPC treatment. WJ-644A is a novel UPR activator that has potential therapeutic value for CRPC.